DEVELOPING AN ACTIVE THINKING ENVIRONMENT AND STRATEGIC DECISION-MAKING SKILLS IN MILITARY EDUCATION - Turakhujaev, Orif Sirojiddinovich (Oriental Journal of Education, 2025)
The article provides a theoretical and practical analysis of creating an active thinking environment and developing strategic decision-making potential in modern military education. The author substantiates the role of the teacher not as a traditional “instructor-preacher,” but as a moderator who organizes and stimulates the process of thinking. The paper explores the ways of cultivating critical and strategic thinking, analytical skills, forecasting ability, moral stance, and a sense of responsibility among future officers through the use of cognitive-interactive technologies such as the case method, problem-based tasks, simulation exercises, the “Think–Pair–Share” technique, mind maps, and visual analysis. Furthermore, the study demonstrates that the harmonious interaction of internal factors (intellectual ability, motivation, metacognitive activity) and external factors (educational environment, pedagogical relations) plays a decisive role in enhancing the professional potential of officers.